2004
DOI: 10.1016/j.immuni.2004.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Imprints Gut-Homing Specificity on T Cells

Abstract: For a preferential homing of T cells to the gut, expression of the integrin alpha4beta7 and the chemokine receptor CCR9 is essential and is induced by antigenic stimulation with dendritic cells from the gut-associated lymphoid organs. Here, we show that the vitamin A (retinol) metabolite, retinoic acid, enhances the expression of alpha4beta7 and CCR9 on T cells upon activation and imprints them with the gut tropism. Dendritic cells from the gut-associated lymphoid organs produced retinoic acid from retinol. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

62
1,591
5
16

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,396 publications
(1,698 citation statements)
references
References 51 publications
62
1,591
5
16
Order By: Relevance
“…Similar to our observations for the co-cultures with organ-specific DC, induction of P-lig expression on Treg under the influence of polarizing factors was less stringently controlled, with IL-12 having only an additive effect. This was in contrast to E-lig expression, which was suppressed upon addition of RA, as has been reported previously for conventional T cells [25]. Although it had been reported that in conventional T cells both regulation and function of E-and P-lig is largely overlapping [11,52], our current findings suggest that Treg display a differential regulation of the two functional selectin ligands.…”
supporting
confidence: 80%
See 3 more Smart Citations
“…Similar to our observations for the co-cultures with organ-specific DC, induction of P-lig expression on Treg under the influence of polarizing factors was less stringently controlled, with IL-12 having only an additive effect. This was in contrast to E-lig expression, which was suppressed upon addition of RA, as has been reported previously for conventional T cells [25]. Although it had been reported that in conventional T cells both regulation and function of E-and P-lig is largely overlapping [11,52], our current findings suggest that Treg display a differential regulation of the two functional selectin ligands.…”
supporting
confidence: 80%
“…Among the molecular factors that control the induction of HR on T cells, RA has recently been shown to play a critical role for the generation of gut-tropic T cells [25]. Only intestinal DC, but not splenic DC expressed retinoid dehydrogenase enzymes, catalyzing the sequential oxidation of vitamin A via retinal to RA, which in turn induced T cell expression of a 4 b 7 and CCR9.…”
Section: Migration Behavior Of In Vitro Modulated Tregmentioning
confidence: 99%
See 2 more Smart Citations
“…Dietary components likely also influence the development of the mucosal immune system in many ways, including stabilization of the microbiota. RA, a metabolite of dietary component vitamin A, has been shown to educate the mucosal DC to imprint primed T cells and B cells with gut tropism [21][22][23][24]. Recent reports further demonstrated that intestine is enriched for DC expressing RA metabolizing enzyme ALDH1a and that RA is a key regulator of TGF-b dependent immune responses by promoting Treg differentiation and inhibiting Th17 cell development [9,11].…”
Section: Introductionmentioning
confidence: 99%